Agromorphological Traits and Comparative Performance For Boosting Yields in Wheat (Triticum Aestivum L.) Germplasm and Cluster Analysis (Bangladesh Journal of Botany, 2022)
In the present study forty nine wheat collections characterized agromorphologically revealed high magnitude of genetic variability in 19 traits. Descriptive statistics demonstrated number of tillers was high from 3.90 - 8.26 with Mean ± SE 5.67 ± 0.13 and SD 0.92. Iqbal 2002 was the early maturing variety with 176 days following Bahawalpur 79 took 191 days to mature. Potohar 70 produced highest yield/plant (19.05 g) while lowest by Iqbal 2002 (8.05 g). Selection could be made per plant yield for promising plants for breeding purposes. Analysis of variance showed that 16 quantitative traits were significant except 02 while six qualitative traits were also significant excluding 02. Two distinct clusters were formed based on Euclidean distances for dissimilarities. Two varieties Potohar 70 and ANZA+2NS were found to be best performer for yield and yield related traits hence are recommended for crop improvement programs.Bangladesh J. Bot. 51(1): 23-28, 2022 (March)